2011
DOI: 10.1002/chem.201003327
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Calix[4]arene‐Supported [MnIII2MnII2] Clusters

Abstract: In the cone conformation calix[4]arenes possess lower-rim polyphenolic pockets that are ideal for the complexation of various transition-metal centres. Reaction of these molecules with manganese salts in the presence of an appropriate base (and in some cases co-ligand) results in the formation of a family of calixarene-supported [Mn(III)(2)Mn(II)(2)] clusters that behave as single-molecule magnets (SMMs). Variation in the alkyl groups present at the upper-rim of the cone allows for the expression of a degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
39
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 52 publications
5
39
2
Order By: Relevance
“…For example, the intention to increase substantially the total spin of the complex led to the synthesis of manganese cluster Mn 19 spin S = 83/2, which, however, did not possess the properties of bistability [7]. The Brechin's group, which earlier synthesized complex Mn 6 with the improved characteristics, recently [8] obtained and characterized a family of calix [4]arene-containing mixed valence tetranuclear manganese complexes, exhibiting properties of molecular magnet at a temperature 61.1 K. Calixarenes are available polydentate ligands with the structural potential for their modification (variation of substituents, bridging fragments between the phenyl rings, and amount of structural units in the calixarene molecule) [9][10][11]. In addition, calixarene-containing [Mn II 2 Mn III 2 ] clusters can be modified by the variation of the monodentate external ligands.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the intention to increase substantially the total spin of the complex led to the synthesis of manganese cluster Mn 19 spin S = 83/2, which, however, did not possess the properties of bistability [7]. The Brechin's group, which earlier synthesized complex Mn 6 with the improved characteristics, recently [8] obtained and characterized a family of calix [4]arene-containing mixed valence tetranuclear manganese complexes, exhibiting properties of molecular magnet at a temperature 61.1 K. Calixarenes are available polydentate ligands with the structural potential for their modification (variation of substituents, bridging fragments between the phenyl rings, and amount of structural units in the calixarene molecule) [9][10][11]. In addition, calixarene-containing [Mn II 2 Mn III 2 ] clusters can be modified by the variation of the monodentate external ligands.…”
Section: Introductionmentioning
confidence: 97%
“…Although coordination in OH-free calixarenes at the lower rim involving the phenol oxygens is a common coordination mode2021, we speculated that the high symmetry and univocal formation of polyhedral cages would prevail over other modes of coordination. Indeed, hexameric self-assembled aggregates and capsules arising from calixarenes or resorcinarenes with other lanthanides and transition metals have been widely studied22232425.…”
mentioning
confidence: 99%
“…The ability to influence the formation of paramagnetic metal ion clusters from multicomponent systems is a challenging synthetic goal that holds great potential when considering the possibility to control or fine tune physical properties such as molecular magnetism (1-5). We have found that methylene-bridged calix [4]arenes (cyclic tetraphenols, collectively termed C [4]s hereafter, Figure 1A), are remarkably versatile ligands for cluster synthesis under ambient conditions, affording a wide range of structural topologies as a result (6)(7)(8)(9)(10)(11)(12). This is primarily due to their possessing a tetraphenolic pocket that readily binds 3d or 4f metal ions when deprotonated with a suitable base.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this is far outwith the scope of this manuscript, but the reader is directed to recent reviews on the subject (18)(19)(20). binding in the tetraphenolato pocket, as well as phenolato and hydroxide bridging to a body Mn II ion (7,11). C) Schematic of dihomooxacalix [4]arene showing the distortion to the lower-rim tetraphenolato binding pocket through introduction of one ethereal bridge, the result of which is a trapezoidal binding pocket.…”
Section: Introductionmentioning
confidence: 99%